Using Video Technology with Flipped Teaching to Explore University Students’ Perception of Their SRL and Instructors’ TPACK - Syh-Jong Jang (Fakultas Tarbiyah Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
This study determines how the use of videos and a blended flipped class model at a university affects university students’ self-regulated learning (SRL) and the instructor’s technological pedagogical and content knowledge (TPACK). The proposed flipped model uses videos in-class, instead of before class, as is the case for the traditional model. This study uses mixed-method research with a case study for one university course. The results indicate that there is a significant difference in SRL and TPACK and that the videos for flipped courses are diverse, rich, and attract students’ attention and interest. Watching technology videos is more efficient in class than watching them out of class. Students work together as a learning community to complete tasks, and the instructor uses technology videos to explain the topics, joins student discussion, and uses multiple strategies and abundant videos to demonstrate the relevance of different thematic units in this course. Using videos in flipped classrooms is beneficial to the university instructor’s TPACK.